Personalized Drug Sensitivity Screening for Bladder Cancer Using Conditionally Reprogrammed Patient-derived Cells - Kettunen, Kimmo (My University, 2019)
Muscle invasive bladder cancer (BC) is a malignancy with a high mutational burden, mortality, and costs. Currently, the standard treatment combines cisplatin-based neoadjuvant chemotherapy (NAC) with radical cystectomy. However, there are no clinically validated means or biomarkers to identify patients for whom NAC is beneficial, and thus, there is an unmet need to estimate individual drug responses. Conditional reprogramming (CR) is a cell culturing approach to propagate cells swiftly from primary tumors for further analyses. This study aimed to evaluate the suitability of the CR cultures to recapitulate BC characteristics and their feasibility for personalized drug sensitivity screening. Six CR cultures were established from tumors with varying stage and histology, including five urothelial and one small cell neuroendocrine carcinomas (SmCC). After freezing and thawing, four cultures continued to proliferate and were compared to their parental tumors with DNA/RNA sequencing analyses and immunohistochemical profiling to validate their origin. Two out of four analyzed cultures well corresponded to their parental tumors and underwent drug sensitivity screening. The standard BC chemotherapy agents (for instance, cisplatin and gemcitabine) were efficient against both malignant cultures. Furthermore, the cultures were sensitive to various other traditional chemotherapy drug classes such as taxanes and inhibitors of topoisomerase and proteasome. Interestingly, SmCC cells were also sensitive to statins at low concentrations. Taken together, the CR culture method represents a viable approach for drug sensitivity testing and may serve as a tool when planning more personalized BC treatment strategies in the future.
Keywords: primaarisolujen viljely, syöpälääkkeiden seulontatestit, täsmälääketiede, virtsarakkosyöpä